2023
DOI: 10.1038/s41598-023-31369-2
|View full text |Cite
|
Sign up to set email alerts
|

Production of neutralizing antibody fragment variants in the cytoplasm of E. coli for rapid screening: SARS-CoV-2 a case study

Abstract: Global health challenges such as the coronavirus pandemic warrant the urgent need for a system that allows efficient production of diagnostic and therapeutic interventions. Antibody treatments against SARS-CoV-2 were developed with an unprecedented pace and this enormous progress was achieved mainly through recombinant protein production technologies combined with expeditious screening approaches. A heterologous protein production system that allows efficient soluble production of therapeutic antibody candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The Fab H 3 was found to exhibit a comparable binding affinity (K D = 20 ± 2.6 nM) to its counterpart REGN10987 Fab (K D = 43 ± 4.4 nM) against SARS-CoV-2 RBD. The K D values observed for the REGN10987 Fab are in accordance with previous reports 40 , 41 thereby validating our finding. These results suggest that the replacement of constant domains in a Fab molecule and the C H 3 domain-based heterodimerization does not interfere with the folding and function of the variable domains such that interactions with its antigen are maintained.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The Fab H 3 was found to exhibit a comparable binding affinity (K D = 20 ± 2.6 nM) to its counterpart REGN10987 Fab (K D = 43 ± 4.4 nM) against SARS-CoV-2 RBD. The K D values observed for the REGN10987 Fab are in accordance with previous reports 40 , 41 thereby validating our finding. These results suggest that the replacement of constant domains in a Fab molecule and the C H 3 domain-based heterodimerization does not interfere with the folding and function of the variable domains such that interactions with its antigen are maintained.…”
Section: Resultssupporting
confidence: 93%
“…We have previously shown that the wild type REGN10987 Fab produced using the CyDisCo system is functional and binds to the target antigen SARS-CoV-2 RBD 40 . After ensuring that the REGN10987- based Fab H 3 produced in the cytoplasm of E. coli was natively folded, we empirically investigated whether the molecule developed was functionally active and compared its binding affinity with that of the REGN10987 Fab using Biolayer Interferometry (BLI).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations